2021
DOI: 10.3389/fonc.2021.664429
|View full text |Cite
|
Sign up to set email alerts
|

Pyrotinib Combined With Vinorelbine in HER2-Positive Metastatic Breast Cancer: A Multicenter Retrospective Study

Abstract: IntroductionPyrotinib plus capecitabine has been approved in China for human epidermal growth factor receptor 2 (HER2)-positive metastatic breast cancer (MBC). Meanwhile, vinorelbine is another important chemotherapy option for MBC available in oral and intravenous forms. Thus, pyrotinib plus vinorelbine may represent a new treatment option, particularly for patients with failed capecitabine treatment. This study reported the first real-world data for pyrotinib plus vinorelbine therapy in HER2+ MBC.MethodsHER2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 32 publications
3
27
3
Order By: Relevance
“…The standard chemotherapy agent for combination with pyrotinib or lapatinib is capecitabine, which is mainly based on the fact that capecitabine is the most commonly used chemotherapy drug for mBC patients with resistance to anthracycline and taxanes. 12,[21][22][23] Moreover, both TKIs and capecitabine are oral drugs with much more convenience for patients to take. In real-world clinical practice, for patients who have progressed on previous capecitabine treatment, other chemotherapy agents such as vinorelbine, gemcitabine and taxanes could also be potentially combined with pyrotinib based on their synergistic effect with trastuzumab.…”
mentioning
confidence: 99%
“…The standard chemotherapy agent for combination with pyrotinib or lapatinib is capecitabine, which is mainly based on the fact that capecitabine is the most commonly used chemotherapy drug for mBC patients with resistance to anthracycline and taxanes. 12,[21][22][23] Moreover, both TKIs and capecitabine are oral drugs with much more convenience for patients to take. In real-world clinical practice, for patients who have progressed on previous capecitabine treatment, other chemotherapy agents such as vinorelbine, gemcitabine and taxanes could also be potentially combined with pyrotinib based on their synergistic effect with trastuzumab.…”
mentioning
confidence: 99%
“… 12 Similarly, lapatinib-naïve patients reportedly had a longer PFS than lapatinib-treated patients who received subsequent pyrotinib + vinorelbine therapy. 13 However, another real-world study suggested that pyrotinib provided a significant longer PFS than T-DM1 among patients who initially responded to lapatinib. 14 These results imply that the efficacy of exchanging TKIs might depend on the response to prior TKI treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The median PFS was 13.7 months (95% CI, 9.3–18.2) in this study, comparable to that reported in the phase III trial (12.5 months), further proving the efficacy of pyrotinib [ 9 ]. Vinorelbine has been an alternative combinational agent for pyrotinib in patients with previous exposure to capecitabine [ 53 ].…”
Section: Discussionmentioning
confidence: 99%